Urgensi Pengaturan Peredaran Minuman Beralkohol di Daerah Istimewa Yogyakarta - Ni'matul Huda; Jamaludin Ghafur; Ali Ridho (Jurnal Hukum IUS QUIA IUSTUM, 2015)
This study discusses the urgency of setting up the circulation of alcoholic beverages in DIY formulated in the following three research problems: first, what is the urgency of Yogyakarta Province government in regulating the circulation of alcoholic drinks? Second, what is the basic principles underlying Yogyakarta Province authority to regulate the circulation of alcoholic beverages and what is the best form of legal products to regulate the circulation of alcoholic beverages in the province? Third, what are the materials of the regulations on the distribution of alcoholic beverages in Yogyakarta Province? This research is a normative juridical which uses primary law, secondary law, and tertiary legal materials. The results showed that first, urgency settings of alcoholic beverages is intended as prevention (preventive), risk reduction (preparedness), responsiveness (response), as well as recovery efforts (recovery) from drinking alcoholic beverages. Secondly, the basis of the authority of Yogyakarta Province Government for the Distribution of Alcoholic Beverages regulation is rooted in Law 32 of 2004 and Presidential Decree No. 74 Year 2014. Third, the main points of the materials contain (i) the type and classification of alcoholic beverages; (ii) a ban on the production, distribution, sale and storage of alcoholic beverages; (iii) licensing; (iv) community participation.